1996
DOI: 10.1111/j.1365-2869.1996.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological pupillary noise in narcolepsy

Abstract: SUMMARY Pupillometry has a long but inconclusive history as a means of measuring human alertness. Spontaneous pupillary oscillations in narcoleptics and the sleep deprived are a recognized but quantitatively elusive indication of alertness. Stimulation of the pupillary light reflex (PLR) has provided contradictory or confusing indications of alertness levels. Results from 10 diagnosed narcoleptics and 10 control subjects in which the PLR system was stimulated and a reliable (90%) discriminator derived for clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Erectile dysfunction [15], reduced pupillary oscillations [16], and cardiovascular reactivity dysfunctions [17], which suggest abnormal central modulation of autonomic control, have been reported in human patients. Donald et al reported that catalepsy was associated with co-activation of sympathetic and parasympathetic autonomic systems in narcolepsyecataplexy patients [18].…”
Section: Discussionmentioning
confidence: 98%
“…Erectile dysfunction [15], reduced pupillary oscillations [16], and cardiovascular reactivity dysfunctions [17], which suggest abnormal central modulation of autonomic control, have been reported in human patients. Donald et al reported that catalepsy was associated with co-activation of sympathetic and parasympathetic autonomic systems in narcolepsyecataplexy patients [18].…”
Section: Discussionmentioning
confidence: 98%
“…The interpretation of pupillometry-derived measures of sleepiness is limited by a lack of normative data and a robust “single-best” measure. Several pupillometry-derived measures of sleepiness, e.g., pupillary diameter and stability, pupillary light reflex have been examined in narcolepsy with discrepant results (Kollarits et al, 1982; Pressman et al, 1984; Norman and Dyer, 1987; O’Neill et al, 1996). …”
Section: Introductionmentioning
confidence: 99%
“…The determination of λ is a key stochastic optimization step. The method we use to determine λ is the same as the one we employed in our narcoleptic study [4] and is summarized in the Appendix. In brief, the discount factor λ is chosen to maximize the estimated Kullback-Leibler divergence function between sleepy and rested subjects [15].…”
Section: Methods Inf Med 3/2003mentioning
confidence: 99%
“…Multiple sleep latency testing of juveniles to assess sleepiness is notoriously problematic so there is an obvious need to develop a rapid and objective measure of sleepiness in children. Previous studies of sleepiness, attention state, and cognition using pupillographic methods have been successful in detecting narcolepsy in adults [4], memory deficits in adults [5], and cognitive memory constraints in adults [6]. A recent pupillographic study under fixed illumination [7] found that prolonged sleep deprivation (> 24 hours) tended to increase a pupillary unrest index which apparently is a measure of the nonstationary pupil size variance.…”
Section: Introductionmentioning
confidence: 99%